Functional and Cognitive Impairment in Patients with Relapsing–Remitting Multiple Sclerosis: Cognitive Tests and Plasma Neurofilament Light Chain Levels - Elina Polunosika; Joel Simren; Arta Akmene; Nikita Klimovskis; Kaj Blennow; Daina Pastare; Henrik Zetterberg; Renars Erts; Guntis Karelis (Medicina)
Background and Objectives: Multiple sclerosis (MS) is a chronic inflammatory, autoimmune, and neurodegenerative disease of the central nervous system. The disease can manifest and progress with both physical and cognitive symptoms, affecting the patient’s daily activities. The aim of our study was to investigate the correlation between functional status, cognitive functions, and neurofilament light chain levels in plasma in MS patients. Materials and Methods: In a cross-sectional study, MS patients with a relapsing–remitting course (according to McDonald’s criteria, 2017) (n = 42) from Riga East University Hospital and a control group (n = 42) were included. In the MS group, the functional status was determined using the Expanded Disability Status Scale (EDSS), and neurofilament light chain levels in plasma (pNfL) were detected using single molecule array (Simoa) technology. The symbol digit modalities test (SDMT), brief visuospatial memory test—revised (BVMT-R), and the nine-hole peg test (9-HPT) were performed on the MS and control groups, dividing the groups by education level. Results: On the SDMT spreading speed, the MS group performed worse than the control group. The median score for the control group was 94.0, and for the MS group, it was 81.3. Slower performance on the SDMT also correlated with a higher EDSS in the MS group. Cognitive processing speed and memory were better in the control group and among individuals with higher education in both groups. For the BVMT-R, we found no difference between the two groups; both groups were able to learn the task equally well, but we found a weak correlation between age and learning in both groups, which could be related to the normal aging process. Execution reaction speed on the 9-HPT with the dominant hand was slower in the MS group (24.1 s) than in the control group (19.4 s). In the MS group, we observed a trend between SDMT performance and pNfL levels: higher pNfL levels were found in individuals who performed more slowly on the SDMT. Conclusions: Cognitive and fine motor dysfunction correlates with neurological impairment and plasma neurofilament light chain levels in MS patients.